Smart grid : communication-enabled intelligence for the electric power grid - Bush, Stephen F. (Chichester, West Sussex : Wiley : IEEE, 2014)
"This book explores the smart grid from generation to consumption; both as it is planned today and how it will likely evolve tomorrow"--
Includes bibliographical references and index.
Keywords: Smart power grids